Reasons for People to Throw Garbage Carelessly in The River of Sea I Village North Sulawesi Based on Law No. 18 of 2008 - Feibe Engeline Pijoh; Janeman Jehezkiel Lanawang; Yoan Barbara Runtunuwu; Romi Mesra (Ideas Publishing, 2023)
Every year, the level of public consumption rises, affecting the frequency with which garbage is created from each action performed. The purpose of this research is to find out how is reasons for people to throw garbage carelessly in the River of Sea I Village. This study uses qualitative research methods. The results of this study indicate that the reasons why people litter are as follows: Imitate what most people do. There is still a lack of understanding of the consequences of unmanaged waste. Feeling lazy to throw garbage in its place. And the lack of waste. It is hoped that the results of this research will contribute to relevant scientific disciplines such as law, sociology, politics, etc., especially for society in general.